Educational Attainment and Fertility in Nepal: An Application of Intermediate Variables Framework - Suwal, Bhim Raj (Tribhuvan University Journal, 2010)
Not available. Key words: Fertility in Nepal; Population change; Nepal Tribhuvan University Journal Volume XVI, 1993 Page: 59-70 Uploaded date: 3 October, 2010